2020
DOI: 10.1177/0269215520954344
|View full text |Cite
|
Sign up to set email alerts
|

Is independence enough? Rehabilitation should include autonomy and social engagement to achieve quality of life

Abstract: Purpose: This discussion paper argues that holding independence as the central goal for rehabilitation has limitations that hinder successful outcomes. It shows why autonomy and social engagement should also serve as goals of rehabilitation, in order to achieve quality of life and effective functioning. Methods: The paper reviews problems arising from the over-emphasis on independence in rehabilitation. Although independence is a valuable goal on some tasks, it is sometimes not possible or desirable and is bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
(103 reference statements)
0
11
0
1
Order By: Relevance
“…Medical rehabilitation treatment contributes to this adaptation and helps preventing, reducing and eliminating limitations caused by this health condition. 1,2 Research has shown that effective rehabilitation consists of two types of intervention: (1) exercise, and (2) self-management and education. 1 Interventions in self-management and education include gaining knowledge about the condition, about consequences of this condition, and learning skills in order to deal with them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical rehabilitation treatment contributes to this adaptation and helps preventing, reducing and eliminating limitations caused by this health condition. 1,2 Research has shown that effective rehabilitation consists of two types of intervention: (1) exercise, and (2) self-management and education. 1 Interventions in self-management and education include gaining knowledge about the condition, about consequences of this condition, and learning skills in order to deal with them.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Research has shown that effective rehabilitation consists of two types of intervention: (1) exercise, and (2) self-management and education. 1 Interventions in self-management and education include gaining knowledge about the condition, about consequences of this condition, and learning skills in order to deal with them. 1 The overall aim of rehabilitation is to improve a person's self-regulation, societal participation, and health-related quality of life (HRQoL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, there has been a societal shift towards focusing health, disability and education supports to go beyond decreasing symptoms and dependence and towards optimizing participation and engagement in important life situations [ 6 , 7 , 8 ]. Arguably, the most influential conceptual framework introduced to assist interprofessional stakeholders across sectors to make this transition is the International Classification of Functioning, Disability and Health (ICF [ 7 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for many people following impairment, whether due to compromised cognitive, social or physical function, exercising autonomy is not through 'doing' the act unassisted, but through participating in interactive relationships with support workers, challenging the traditional view in rehabilitation of pursuing independent, unassisted, autonomy (Gibson, 2014;McClure & Leah, 2020). Such relationships extend beyond a transactional nature and are characterised by a number of subtle and complex characteristics.…”
Section: Introductionmentioning
confidence: 99%